Pilot peer health education for noncommunicable disease prevention in Bangladesh, Ethiopia, and Palau - Lemlem W Gebremariam; Yoshihisa Hirakawa; Shahrin E Rayna; Fahmida A Khan; Chifa Chiang; Yupeng He; Everlynn J Temengil; Sherilynn Madraisau; Md Khalequzzaman; Sohel R Choudhury; Hiroshi Yatsuya; Atsuko Aoyama (Journal of Global Health Reports)
# Background